Hubungan antara Kebiasaan Makan dan Kebiasaan Olahraga dengan Pertumbuhan Fisik dan Kesehatan Reproduksi: The Relationship between Eating Habits and Exercise Habits with Physical Growth and Reproductive Health - Ramesia Ratnawati Rames; Yessy Octa Fristika (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2026)
Adolescence is a crucial phase in human development. This period is marked by the transition from childhood to adulthood, involving biological, psychological, and social changes. Attention to diet is crucial for adolescents because it influences growth and reproductive health. Furthermore, physical activity, such as exercise, plays a role in supporting physical growth. This study aims to analyze the relationship between eating habits and exercise habits with the physical growth and reproductive health of adolescents. This study used a descriptive design with a cross-sectional approach. The analyses used univariate and bivariate analyses. The sample was taken using total sampling. The total sample size for this study was 84 individuals. The results of the study showed a significant relationship between eating habits and physical growth (P-value = 0.005). There was no relationship between eating habits and reproductive health (P-value = 0.929). There was a significant relationship between exercise habits and physical growth (P-value = 0.043), and there was a significant relationship between exercise habits and reproductive health (P-value = 0.002). It was concluded that there is a fairly strong relationship between eating habits and exercise habits on physical growth, as well as exercise habits on reproductive health.